Computer Grading of English Composition. - Daigon, Arthur (Education Digest, 1966)
The article focuses on the computer grading of English composition. Keeping books and inventories, processing payrolls, assigning student programs--these repetitive, arithmetic chores are now accepted as falling within the province of the computer. But reading and evaluating that complex symbolic process we call language surely must be a presumptuous incursion into realms strictly assigned to the human intellect. The computer should be considered not as a teacher replacement but ultimately as an aid to overburdened English teachers, a device which will, when fully developed, not only give the teacher significant data but will facilitate the very "feedback" teachers say machines discourage. An example or two will illustrate how punctuation can be checked. A more difficult challenge is to have the machine distinguish between the uses of there and their, the most common error in written usage. Clues to specific indicators of mature style were suggested by readability formulas, which attempt to predict the reading difficulty of prose selections based on their comprehension by various groups of readers. To determine a student's mode of organization, the detection of key words and phrases would modulate the computer's response. The machine can do no worse; perhaps it can provide overworked teachers with the time and the data required for the individualized teaching of any student, the creative as well as the inarticulate.